2018
DOI: 10.1108/jadee-01-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

The role of farmer organizations and networks in the rice supply chain in Thailand

Abstract: Purpose The purpose of this paper is to examine the development of rice supply chain in the context of the role of rice farmer organizations and cooperative networks in Thailand. Design/methodology/approach Primary data were solicited from the cooperatives and members of cooperatives for this study through questionnaire administration. The questionnaire containing a five-point Likert scale was posed to respondents to ascertain their problems before and after joining the network (for cooperative) and after jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 27 publications
4
37
0
1
Order By: Relevance
“…Members' participation in meetings and business of the cooperatives, and flow of information influenced satisfaction of the members (p < 0.01). These results are consistent with previous studies revealed that members' satisfaction with the activities of rural cooperatives activities is dependent on their participation in meetings and business of the cooperative and the resulting benefit of access to production and marketing information (Sathapatyanon and Kuwornu, 2019;Sathapatyanon et al, 2018;Arcas-Lario et al, 2014;Sadighi and Darvishinia, 2005).…”
Section: Determinants Of Members' Satisfaction With the Activities Ofsupporting
confidence: 92%
See 4 more Smart Citations
“…Members' participation in meetings and business of the cooperatives, and flow of information influenced satisfaction of the members (p < 0.01). These results are consistent with previous studies revealed that members' satisfaction with the activities of rural cooperatives activities is dependent on their participation in meetings and business of the cooperative and the resulting benefit of access to production and marketing information (Sathapatyanon and Kuwornu, 2019;Sathapatyanon et al, 2018;Arcas-Lario et al, 2014;Sadighi and Darvishinia, 2005).…”
Section: Determinants Of Members' Satisfaction With the Activities Ofsupporting
confidence: 92%
“…The value of the businesses of the cooperatives, members' investment in shares of the cooperatives, and profitability positively influenced the members' satisfaction with the cooperatives (p < 0.01). The results are consistent with previous studies that profitability of the cooperatives leads to more commitment of the members to the activities of the cooperatives and the more satisfied they become (Sathapatyanon et al, 2018;Dejene and Getachew, 2015;Dejene, 2014;Österberg et al, 2009;Bruynis et al, 2001;Gray and Kraenzle, 1998;Fulton and Adamowicz, 1993). Moreover, services offered by the agricultural cooperatives contribute to increasing its organisational effectiveness and therefore the satisfaction and loyalty of members of the cooperatives Sathapatyanon and Kuwornu, 2019;Sathapatyanon et al, 2018;Promme et al, 2017;Yacob et al, 2016;Mohamed, 2004).…”
Section: Determinants Of Members' Satisfaction With the Activities Ofsupporting
confidence: 92%
See 3 more Smart Citations